2005
DOI: 10.1177/002242940505300406
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sex and Race Identification on Instrument Assignment by Music Educators

Abstract: Erin E. Stewart is a graduate student at the same institution; e-mail: estewart@sunflower.com. Copyright © 2005 by MENC: The National Association for Music Education.The purpose of this study was to investigate the effect of sex and race identification on the assignment of instruments to beginning band students. Participants (N = 201) were music educators solicited by university professors across the United States. Participants completed an online survey about instrument assignments. Half the participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…The resulting order above accords well with an evidence of studies that have investigated variously: attitudes among pre-service and in-service teachers (Abeles and Porter, 1978; Griswold and Chroback, 1981; Tarnowski, 1993; Zervoudakes and Tanur, 1994; Bayley, 2000; Yoder and Kahn, 2003; Johnson and Stewart, 2005; Abeles, 2009), gender stereotyping (Crowther and Durkin, 1982; Lipton, 1987; Byo, 1991; Bruce and Kemp, 1993; Elliot and Yoder-White, 1997; Pickering and Repacholi, 2001; McKeage, 2004; Walker, 2004), and the perceptions of children (O’Neill and Boulton, 1996; O’Neill, 1997; Ryan et al, 2000; De Vous, 2011).…”
Section: Data Collectionsupporting
confidence: 84%
See 1 more Smart Citation
“…The resulting order above accords well with an evidence of studies that have investigated variously: attitudes among pre-service and in-service teachers (Abeles and Porter, 1978; Griswold and Chroback, 1981; Tarnowski, 1993; Zervoudakes and Tanur, 1994; Bayley, 2000; Yoder and Kahn, 2003; Johnson and Stewart, 2005; Abeles, 2009), gender stereotyping (Crowther and Durkin, 1982; Lipton, 1987; Byo, 1991; Bruce and Kemp, 1993; Elliot and Yoder-White, 1997; Pickering and Repacholi, 2001; McKeage, 2004; Walker, 2004), and the perceptions of children (O’Neill and Boulton, 1996; O’Neill, 1997; Ryan et al, 2000; De Vous, 2011).…”
Section: Data Collectionsupporting
confidence: 84%
“…educational and training opportunities, attitudes of teachers and music directors, and lack of female role models in secondary and higher education (Bayley, 2000; Graham, 2005; Johnson and Stewart, 2005; Gould, 2008; Gathen, 2014);…”
Section: Data Collectionmentioning
confidence: 99%
“…Performers’ physical attributes have been linked with adjudicators’ initial impressions (Fredrickson, Johnson, & Robinson, 1998; Robinson, 2000) and assigned performance ratings (Ryan & Costa-Giomi, 2004; Siddell-Strebel, 2007; Wapnick, Darrow, Kovacs, & Dalrymple, 1997; Wapnick, Mazza, & Darrow, 1998, 2000) along with other visual factors including performer race (Elliott, 1995b; Goldin & Rouse, 2000; Johnson & Stewart, 2005; McCrary, 1993), perceived performance status (Duerksen, 1972), choral conductors’ body types (VanWeelden, 2002), and preference for performances with memorized versus nonmemorized music (Siddell-Strebel, 2007; Williamon, 1999). Findings from these studies indicate that visual and nonmusical factors influence adjudicators’ perceptions of performance quality.…”
mentioning
confidence: 99%
“…The distribution of children by grade and band membership is reported in Table 1 and represents approximately two third of the enrollment in the band program at this school. Demographic information was not collected directly from children, since previous research has found no significant effect of race/ethnicity on gender stereotypes (Johnson & Stewart, 2005). However, description of the school may be useful to other educators in determining the similarity of this school, and how likely our findings are to generalize to their own school.…”
Section: Participantsmentioning
confidence: 99%